Ovrednotenje vegetacijske primernosti habitata ruševca (Tetrao tetrix L.) na Pohorju - Gulič, Jurij (Zbornik gozdarstva in lesarstva, 2003)
The Black Grouse inhabits mountain ridges in the western part of the Pohorje Mts (1543 m a., NE Slovenia). In the mating periods (2000, 2001), we carried out a survey of six known pairing areas and thus separated plots of potential habitat. In comparison, two abandoned display grounds were also incorporated. The base sampling areas (400 x 400 m) were divided into 256 square planes. It was discovered that the four active display grounds were relatively homogenous, while the two abandoned grounds clearly differed from them. The differences of the observed vegetation type characteristics (cover of blueberry, cranberry, autumn heather, herb layer, share of pastures including those now being overgrown, the abundance of bush layer, crown density of Norway spruce, mountain ash and anthills) are statistically significant. This declining tendency was noticeable from the display grounds in the west to the abandoned display grounds in the east, from the hinterland of a stable Alpine population towards the edge of the sub-Pannonian phytogeographic region. Cover value of blueberry on active display grounds is 19%, abandoned display grounds 5 %, herb layer 38% (11%), the number of anthills is 13.7/ha (8/ha). A comparison between vegetation types and richness of herbal and shrub layer has shown that the most suitable habitats for the Black Grouse are places with interchanging swampland ecosystems (12%),pastures (15%), partially overgrown pastures (41%), forest (31%) and water areas (1%), although on preliminary condition that the area is not beingfurther overgrown and overpopulated, by human.
Keywords: environmental protection; Pohorje; rastišča; ruševec; Tetrao tetrix L.; varstvo narave; življenjski prostor